The Prehistoric Indian Ayurvedic Rice Shashtika Is an Extant Early Domesticate With a Distinct Selection History - Jose, Mariet; Raj, R. Dinesh; Vinitha, M. R.; Madhu, Remya; Varghese, George; Bocianowski, Jan; Yadav, Rashmi; Patra, B. C.; Singh, O. N.; Rana, J. C.; Kurmari, S. Leena; Thomas, George (Frontiers in Plant Science, 2018)
Abstract Fully domesticated rice is considered to have emerged in India at approximately 2000 B.C., although its origin in India remains a contentious issue. The fast-growing 60 days rice strain described in the Vedic literature (1900-500 B.C.) and termed Shashtika (Sanskrit) or Njavara (Dravidian etymology) in Ayurveda texts including the seminal texts Charaka Samhita and Sushruta Samhita (circa 660 - 1000 B.C.) is a reliable extant strain among the numerous strains described in Ayurveda literature. We here report the results of the phylogenetic analysis of Njavara accessions in relation to the cultivars belonging to the known ancestral sub-groups indica, japonica, aromatic and aus in rice gene pool and the populations of the progenitor species Oryza rufipogon using genetic and gene genealogical methods. Based on neutral microsatellite markers, Njavara produced a major clade, which comprised of minor clades corresponding to the genotypic classes reported in Njavara germplasm, was distinct from that were produced by the ancestral sub-groups. Further we performed a phylogenetic analysis using the combined sequence of 19 unlinked EST-based sequence tagged site (STS) loci with proven potential in inferring rice phylogeny. In the phylogenetic tree also the Njavara genotypic classes were clearly separated from the ancestral sub-groups. For most loci the genealogical analysis produced a high frequency central haplotype shared among most of the rice samples analyzed in the study including Njavara and a set of O. rufipogon accessions. The haplotypes sharing pattern with the progenitor O. rufipogon suggests a Central India–Southeast Asia origin for Njavara. Results signify that Njavara is genetically distinct in relation to the known ancestral sub-groups in rice. Further, from the phylogenetic features together with the reported morphological characteristics, it is likely that Njavara is an extant early domesticate in Indian rice gene pool, preserved in pure form over millennia by the traditional prudence in on-farm selection using 60 days maturity, because of its medicinal applications.